GAMBARAN PERSEPSI MAHASISWA BERDASARKAN JENIS KELAMIN TERHADAP PEMBELAJARAN SKILL LAB SECARA DARING DI FAKULTAS KEPERAWATAN - Isfahani Safril; Gamya Tri Utami; Yesi Hasneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Laboratory skill via online is a competency or students to learn medical skills that are conducted in a training environment then conduct performance (working score) based on the student’s capabilities in using Pedagogy (a teaching method). This research used a Descriptive Quantitative research. These research samples were 169 respondents taken by Stratified Random Sampling. The research used a questionnaire to identified student’s perception on learning lab skills via online. This research used Univariate Analysis. This research gives illustrations of learning lab skills via online. Female students have more positive perception on learning lab skills via online compares with male students. Students’ comprehension on learning lab skills via online is good and could be the solution for the learning activities in the midst of a pandemic.Keywords: Comprehension, Covid-19, Lab skill online.